2022
DOI: 10.1093/gji/ggac299
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of oceanic crust in the Enderby Basin offshore East Antarctica

Abstract: Summary Seismic reflection and refraction data were collected in 2007 and 2012 to reveal the crustal fabric on a single long composite profile offshore Prydz Bay, East Antarctica. A P-wave velocity model provides insights on the crustal fabric, and a gravity-constrained density model is used to describe the crustal and mantle structure. The models show that a 230 km wide continent-ocean transition separates stretched continental from oceanic crust along our profile. While the oceanic crust close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Altenbernd-Lang et al (2022a) used seismic refraction and gravity data along a profile south of Sri Lanka to infer the COB beyond stretched continental crust, and unusually high velocities in the upper mantle of the oceanic crust. Based on seismic reflection and refraction data off Prydz Bay, Altenbernd-Lang et al (2022b) suggested that oceanic crust begins 160 km further south than previously proposed (Figure 2b) and the Mac Robertson Coast Anomaly is not a COB but chron M4.…”
Section: Tectonic Settingmentioning
confidence: 75%
See 3 more Smart Citations
“…Altenbernd-Lang et al (2022a) used seismic refraction and gravity data along a profile south of Sri Lanka to infer the COB beyond stretched continental crust, and unusually high velocities in the upper mantle of the oceanic crust. Based on seismic reflection and refraction data off Prydz Bay, Altenbernd-Lang et al (2022b) suggested that oceanic crust begins 160 km further south than previously proposed (Figure 2b) and the Mac Robertson Coast Anomaly is not a COB but chron M4.…”
Section: Tectonic Settingmentioning
confidence: 75%
“…Based on seismic reflection and refraction data off Prydz Bay, Altenbernd‐Lang et al. (2022b) suggested that oceanic crust begins 160 km further south than previously proposed (Figure 2b) and the Mac Robertson Coast Anomaly is not a COB but chron M4.…”
Section: Tectonic Settingmentioning
confidence: 92%
See 2 more Smart Citations